COMMUNICATION WITH STUDENTS AND PEDAGOGICAL PSYCHOLOGY IN TUTORING ACTIVITIES - Khaitov Sherzod Komilovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Effective communication and pedagogical psychology play a vital role in tutoring, ensuring that students receive the guidance and support necessary for academic success. This paper explores key aspects of communication, including verbal and non-verbal interactions, active listening, and constructive feedback, which enhance student engagement and comprehension. Additionally, it examines the relevance of pedagogical  psychology  in  tutoring,  focusing  on  learning  styles,  motivation,  and emotional intelligence. By integrating these principles, tutors can foster a productive and inclusive learning environment. The study highlights best practices for effective student-tutor interactions, such as building rapport, encouraging active learning, and leveraging  technology.  The  insights  presented  emphasize  the  necessity  of  a psychologically  informed  approach  to  tutoring,  ultimately  empowering  students  to become independent and confident learners.